The Effectiveness of Scientific Approach and Contextual Teaching and Learning Approach in Teaching Writing - Indrilla, Nidya (Bina Nusantara University, 2018)
This research used a quasi-experimental design. The population was grade VIII students of SMP XX Yogyakarta that consisted of four classes. The sample consisted of three classes, namely class 8A using CTL approach and class 8B using the scientific approach as the experimental groups, while class 8D used the conventional approach as the control group. The instruments used were tests in the form of writing composition. The hypotheses testing were analyzed using ANCOVA test. The results are (1) there are significant differences in writing achievement among the students taught by using the scientific approach, CTL approach, and conventional approach. (2) The use of the scientific approach and the CTL approach are more effective than that of the conventional approach in teaching writing. (3) The use of the scientific approach is not more effective than that of the CTL approach in teaching writing.Â